ҚАРАҚАЛПАҚ ЖЫРАЎЫ: УСТАЗ-ШӘКИРТ ДӘСТУРИ - Алламбергенов, К.; Палымбетов, К.С. (FAN va JAMIYAT, 2021)
The article is about the folk glottal singers – (zhyrau), which has a special place in the history of the Karakalpak people. The author analyzes, based on traditions, how teacher-pupil takes place for the transfer of folk epic from generation to generation. From a scientific point of view, the traditions of the art of folk singing, pupils among young people in the tradition of a teacher-pupil and the study of the epic in a verbal form.